Plant kinesin-12: Localization heterogeneity and functional implications - Livanos, Pantelis; Müller, Sabine (International Journal of Molecular Sciences, 2019)
Kinesin-12 family members are characterized by an N-terminal motor domain and the extensive presence of coiled-coil domains. Animal orthologs display microtubule plus-end directed motility, bundling of parallel and antiparallel microtubules, plus-end stabilization, and they play a crucial role in spindle assembly. In plants, kinesin-12 members mediate a number of developmental processes including male gametophyte, embryo, seedling, and seed development. At the cellular level, they participate in critical events during cell division. Several kinesin-12 members localize to the phragmoplast midzone, interact with isoforms of the conserved microtubule cross-linker MICROTUBULE-ASSOCIATED PROTEIN 65 (MAP65) family, and are required for phragmoplast stability and expansion, as well as for proper cell plate development. Throughout cell division, a subset of kinesin-12 reside, in addition or exclusively, at the cortical division zone and mediate the accurate guidance of the phragmoplast. This review aims to summarize the current knowledge on kinesin-12 in plants and shed some light onto the heterogeneous localization and domain architecture, which potentially conceals functional diversification.
CRIS-Team Scopus Importer:2021-07-01
Keywords: Cytokinesis; Division plane determination; Gametogenesis; Microtubules; Phragmoplast midzone